Debridement without bone grafting prevents osteolytic lesions progression in revision THAs with prosthesis revised - Kong, Keyu; Li, Fupeng; Qiao, Hua; Chang, Yongyun; Hu, Yi; Li, Huiwu; Zhang, Jingwei (Frontiers in Surgery, 2023)
Abstract Background: Bone defects in revision total hip arthroplasties (rTHAs) caused by osteolysis are routinely treated with autografts or allografts, despite their various disadvantages. Currently, little is known about the prognosis of ungrafted cavities with complete debridement following prosthetic revision in rTHAs with component loosening, as few reports have focused on the application of debridement without bone grafting in osteolytic lesions that do not compromise structural stability in revision THAs with revised components. Methods: In this study, 48 patients receiving rTHAs with components revised for aseptic loosening with osteolysis between 2015 and 2019 were included. Anteroposterior and lateral radiographs of hips before and after revision surgery and last follow-up were compared to measure whether the size of debrided osteolytic cavity without bone graft had changed. Results: In total, 48 patients with 59 osteolytic lesions were enrolled. The mean follow-up period was 3.33 years (range 2-6 years). None of the 59 cavities had progressed at the last follow-up, and 11 (18.6%) regressed. Two patients underwent re-revision according to dislocation during follow-up. Conclusion: In rTHAs with revised components, osteolytic lesions that do not influence structural stability could be debrided without grafting to avoid the disadvantages of grafting. Debridement and component revision are sufficient to prevent the progression of osteolytic lesions during surgery, without having adverse effects on the short-to mid-term prognosis.